PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL CONCEPTUAL UNDERSTANDING PROCEDURES DALAM MENINGKATKAN PENGUASAAN KONSEP IPA FISIKA SISWA DI KELAS VIII SMP - Rezi Pratiwi; M. Rahmad M. Rahmad; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning tools developed are the Conceptual Understanding Procedures model learning tools in improving the mastery of science and physics concepts on work and simple planes in class VIII Junior High School, consisting of Learning Plans and Student Worksheets. The purpose of this research is to produce a valid Conceptual Understanding Procedures learning device that is used to improve the mastery of the concepts of science and physics on work and simple planes in class VIII Junior High School. This research is expected to be a reference for making innovative learning tools and can be used as a basis in the teaching and learning process so that learning objectives can be achieved. This type of research is development research using the Hannafin and Peck (H&P) model.. This research is only limited to the development stage. The research instrument used was the Learning Plans and Student Worksheets validation assessment sheets which were used by the validator to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. The results showed that the Conceptual Understanding Procedures learning device model was declared valid with an average RPP score of 3.25 in the very high category and the LKPD score of 3.30 in the very high category. mastery of students' concepts on work and simple planes. Key Words: Science Learning Tools, Model Conceptual Understanding Procedures, Mastery of Concepts, Work and Simple Planes